Harga Saham Sebelum dan Sesudah Stock Split - Junita Putri Rajana Harahap; Murni Dahlena Nasution (COSTING : Journal of Economic, Business and Accounting, 2020)
The stock split causes the stock price to be cheaper so that it will attract potential investors to buy the stock. This research was conducted to determine when it is time for a company to do a stock split, information available on the capital market can be used by investors for consideration before investors make a decision to invest in shares. The study aims to determine the changes that occur in stock prices before and after the stock split policy by the company. The research method used in this research is event study research with a quantitative approach. This study examines how significant the stock price difference is after a stock split policy. The sample used in this study were all companies that carried out the 2016-2018 stock split policy. The results of research on companies that become samples have shown that the average stock price before the announcement of the stock split policy has no significant difference with the average stock price after the announcement of the stock split policy Keywords : Stock Price, Stock Split